Effects of COVID-19 and diabetes mellitus on AMPKα1 and IRS-1 amount in the blood plasma of patients - Tronko, M.D.; Pushkarev, V.V.; Sokolova, L.K.; Cherviakova, S.A.; Belchina, Y.B.; Kovzun, O.I.; Guda, B.B.; Pushkarev, V.M. (Доповіді НАН України, 2022)
The aim of the study was to determine the levels of AMPKα1 and IRS-1 in the blood of patients with diabetes mellitus
and COVID-19. AMPKα1 and IRS-1 were determined using enzyme-linked immunosorbent assay (ELISA) (Elabscience,
USA). AMPK controls the energy balance of the cell, stimulates catabolic processes – absorption of glucose, fatty
acids, and their conversion by mitochondrial oxidation and glycolysis. With type 2 diabetes and obesity, its activity decreases,
and the activity of protein kinases mTORC1/p70S6K increases, leading to phosphorylation of insulin receptor
substrate-1 (IRS) and insulin resistance. The level of AMPKα1 in the blood of diabetic patients was significantly higher
than in the blood of healthy people. The amount of AMPKα1 in the blood of people recovered from COVID-19 demonstrated
the further growth of AMPKα1. The level of AMPKα1 was much higher in the blood of patients with DM during
a COVID-19 disease. IRS-1 amounts in the blood plasma of patients with diabetes was higher than normal values. The
level of IRS-1 in the blood plasma of patients with COVID-19 was much higher than in the blood of healthy people and
patients with diabetes. The level of IRS-1 in the blood plasma may be one of the promising markers of COVID-19. Досліджено рівень AMPKα1 та IRS-1 у крові хворих на цукровий діабет та COVID-19 (n = 81). Кількість
AMPKα1 та IRS-1 визначали за допомогою імуноферментного аналізу (Elabscience, США). AMPK контролює енергетичний баланс клітини, стимулює катаболічні процеси — поглинання глюкози, жирних кислот і їх перетворення шляхом мітохондріального окиснення та гліколізу. У разі цукрового діабету 2-го типу та ожиріння її активність знижується, а активність протеїнкіназ mTORC1/p70S6K підвищується, що призводить до фосфорилювання субстрату інсулінового рецептора-1 (IRS) і резистентності до інсуліну. Встановлено, що рівень AMPKα1 у крові хворих на цукровий діабет був значно вищим, ніж у крові здорових
людей. У крові людей, які одужали від COVID-19, виявлено подальше зростання AMPKα1. У крові пацієнтів із цукровим діабетом під час захворювання на COVID-19 рівень AMPKα1 був значно вищим. Кількість IRS-1 у плазмі крові пацієнтів з цукровим діабетом була вищою за нормальні значення. У плазмі
крові хворих на COVID-19 рівень IRS-1 був значно вищим, ніж у крові здорових людей та хворих на цукровий діабет. Рівень IRS-1 у плазмі крові може бути одним із перспективних маркерів COVID-19.